Aboriginal student engagement and success in Kimberley tertiary education. Issue 2 (26th December 2021) - Guenther, John; Dwyer, Anna; Wooltorton, Sandra; Wilks, Judith
Abstract: Over recent years, considerable effort has been put into increasing Aboriginal and Torres Strait Islander (First Nations) participation in higher education. While there are signs that enrolments are increasing, the sustained engagement and successful completion of higher education remains challenging, particularly in remote locations. With this in mind, a collaborative research project among researchers from three northern Australian tertiary education institutions was designed to understand student perspectives, particularly from remote contexts, about their engagement and success towards completion in higher education. Based on a qualitative research design situating Indigenist/interpretive research within a critical realism metatheory, we present findings from the study, based in the Kimberley region of Western Australia, and unpack implications for higher education provision in remote contexts. The findings point to the unique challenges faced by students who live in the Kimberley—and perhaps in other remote locations around Australia. In order to meet these needs, we suggest that tertiary education providers must tailor provision to ensure that engagement with Aboriginal students is relational and culturally safe.